Professional Quality of Life (ProQOL) of Health Care Providers in Manipur, India - Mathew, Lintu; Gupta, Avantika (National Journal of Community Medicine, 2023)
Introduction: Professional Quality of Life (ProQOL) relates to comfort and satisfaction in a profession. Health care providers are exposed to great level of stress and traumatic events in their job. This study aimed at determining the ProQOL of health care providers in Bishnupur district. Methodology: A cross sectional study was conducted among health care providers of Bishnupur district, Manipur during 24 January- 24 February 2021. The participants were 153 healthcare providers from district hospital, CHCs and PHCs using a convenience method. The instrument for collecting data consisted of “Professional Quality of Life Measure version 5(ProQOL-5)” questionnaire. Chi square test and Pearson’s r correlation was used for analysis. Results: Mean age of the participants was 37.54 + 9.1 years. The mean values for the domain compassion satisfaction (CS), secondary traumatic stress (STS), burnout (BO) was 36.7 + 5.2, 23.2+ 4.5 and 23.3 + 5.6 respectively. BO and STS were positively correlated. There was no significant association between other domains. Participants who had night shifts had more BO level compared to others. Conclusion: Majority of the participants had moderate CS and STS. Those having prolonged duty hours experienced more burnout compared to others.